Deep neck space infections: Risk factors related with length of stay and presence of complications - Ferreira, Filipa (2021)
Objectives: Analyse risk factors related to length of stay in a selection of patients with cervical abscesses and identify predictors for complications.  Study design: Retrospective study.  Material and methods: Study of cervical abscesses in adults admitted to the ENT service at Hospital Garcia Orta from 2014 to 2019.  Results and Conclusions: 146 patients were identified. Advanced age, comorbidities such as hypertension or diabetes, dyspnoea on admission, size of the abscess, non-periamygdalin location, need to change antibiotic or non-transoral drainage route were statistically associated with longer hospital stay and complications. Creatinine, urea and increased CRP at admission were identified as predictors of complications.  The approach to patients with suspected cervical abscess should consider the assessment of factors that may alert to a higher risk of complications or to a longer hospital stay, as shown in the present study.